Hubungan Jarak Kehamilan Ibu Dengan Kejadian Anemia Di Puskesmas Kencong Kabupaten Jember - Hani Pramita; Rani Safitri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Anemia in pregnant women is a national health concern that reflects the socioeconomic conditions of a population and has a significant impact on the quality of human resources. This condition poses a high risk to both maternal and fetal health, thus requiring serious attention from healthcare providers. According to the World Health Organization (WHO), anemia occurs when hemoglobin levels or the number of red blood cells fall below the normal range. At Kencong Community Health Center in Jember Regency, pregnant women with interpregnancy intervals of less than two years showed a higher tendency to experience anemia and pregnancy-related complications. This study applied a correlational design with a cross-sectional approach, involving a population of 83 pregnant women, from which 32 participants were selected using purposive sampling. Data were collected using observation sheets and checklists, then analyzed using the Chi-Square test. The results revealed that all pregnant women with interpregnancy intervals of less than two years were anemic, while no cases of anemia were found among those with spacing of more than two years. A p-value of 0.000 indicated a highly significant relationship between pregnancy spacing and the incidence of anemia. Therefore, it is recommended that women maintain a minimum two-year interval between pregnancies to allow for nutritional recovery and to prevent anemia in subsequent pregnancies.